Identifying the effect of climate change on desertification in northern China via trend analysis of potential evapotranspiration and precipitation. (May 2020) - Zhang, Caixia; Wang, Xunming; Li, Jinchang; Hua, Ting
Highlights: Desertification and its causes are dynamic processes. Desertification is driven by a combination of climate change and human factors. Main driving factors can be determined based on scenarios establishment. Desertification driving factors should be analyzed in a spatiotemporal sense. Abstract: Desertification and its causes are dynamic processes, which therefore make it necessary to discuss the factors that drive desertification in a specific spatiotemporal sense. Here the temporal trends in potential evapotranspiration (PE) and precipitation were selected as climate change indicators, five possible scenarios were established and relationships between desertification and the climate change indicators were examined for different time periods across northern China. The results indicate that climate change was the primary or one of drivers of desertification reversion in the northeastern and northwestern regions of China between 1975 and. 1990, whereas the desertification reversion near Mu Us Desert was influenced primarily by human intervention. Climate change triggered desertification variation across the entire region, including the Hulenbur, Otigdag, Horqin, Horbq, and Mu Us deserts and the Sounite Grassland between 1990 and 2000. However, the desertification reversion near the Otindag, Mu Us and Horqin deserts was due primarily to human intervention. Desertification reversion occurred across 54, 609 km 2 between 2000 and 2005 in northern China and climate change was thought to be related to majority reversion, whereas the regions that experienced desertification development and aggravation, including the areas near the Hulunbuir and Nengjiang deserts, were influenced primarily by human intervention. Broad desertification reversion occurred across the North China region between 2005 and 2010, with 45, 787 km 2 experiencing desertification reversion compared with only 8026 km 2 experiencing desertification development and aggravation, however, climate change had a limited effect on desertification in this period. The study provides a new understanding of the causes of desertification, and an easier and more effective framework for determining the role of climate change on desertification.